Prediction of cardinal temperature by nonlinear regression models in carrot (Daucus carota L.) and three common weed species - مرجان دیانت (علوم و فناوری بذر ایران, 2019)
Carrot is a particularly difficult crop to manage in terms of weed control. For weed management of carrot, seed germination is a key process because it determines both the number of weeds that could potentially emerge and the timing of their appearance in the carrot. This study was done to evaluate two nonlinear regression models (Intersected-lines and Dent-like) to describe response of germination rate to temperature in carrot (Daucus carota L.), common chickweed (Stellaria media (L.) Vill.), yellow foxtail (Setaria glauca (L.) P. Beauv.) and canada fleabane (Conyza canadensis (L.) Cronq.). This experiment was based on completely randomized design with 4 replications at Islamic Azad University, Science Research Branch, in 2015. The seeds were treated with different temperatures (2, 5, 10, 15, 20, 25, 30, 35, 40 and 45oC). The analysis of variance showed that temperature had a significant effect on all seed germination percentage and germination rates. Intersected-lines model was superior in carrot and Dent-like model was superior for common chickweed, yellow foxtail and canada fleabane. Base, optimum and maximum temperatures were predicted with appropriate model. Base, optimum and maximum temperatures were for carrot 1.67, 22.84, 43.16; common chickweed 3.58, 18.82-19.67, 42.75; yellow foxtail 14.17, 33.75-34.92, 44.86 and canada fleabane 13.74, 31.73-31.94, 44.21ºC, respectively. This results showed that carrot germinated earliest among the studied species, because it had the lowest base temperature, so sooner planting it was caused sooner carrot establishment and less weed competition.